2022
DOI: 10.1088/1748-9326/ac8754
|View full text |Cite
|
Sign up to set email alerts
|

Attribution of the 2020 surge in atmospheric methane by inverse analysis of GOSAT observations

Abstract: Atmospheric methane mixing ratio rose by 15 ppbv between 2019 and 2020, the fastest growth rate on record. We conduct a global inverse analysis of 2019-2020 GOSAT satellite observations of atmospheric methane to analyze the combination of sources and sinks driving this surge. The imbalance between sources and sinks of atmospheric methane increased by 31 Tg a-1 from 2019 to 2020, representing a 36 Tg a-1 forcing (direct changes in methane emissions and OH concentrations) on the methane budget away from steady s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 48 publications
6
31
0
Order By: Relevance
“…These results are supported by the findings of Qu et al. (2022) from GOSAT retrievals, that 82% of methane growth from 2019 to 2020 was primarily driven by increased emissions rather than [OH] sink reductions, with a large contribution from African wetlands. Similarly, Drinkwater et al.…”
Section: The Wetland Hypothesissupporting
confidence: 84%
See 2 more Smart Citations
“…These results are supported by the findings of Qu et al. (2022) from GOSAT retrievals, that 82% of methane growth from 2019 to 2020 was primarily driven by increased emissions rather than [OH] sink reductions, with a large contribution from African wetlands. Similarly, Drinkwater et al.…”
Section: The Wetland Hypothesissupporting
confidence: 84%
“…Similarly, looking at the surge in growth in 2019–2020, using a global inverse analysis of GOSAT satellite observations, Qu et al. (2022) found the imbalance between sources and sinks of methane increased by 31 Tg in the year 2019–2020. They found that half the growth in methane emissions in 2019–2020 took place in Africa, especially East Africa, most likely from wetlands, with strong emissions growth in Canada also.…”
Section: Inference: Increased Natural Emissions Are a Major Cause Of ...mentioning
confidence: 99%
See 1 more Smart Citation
“…The imagery data provide new information to interpret contemporary changes in the atmospheric growth rate-in our example, year-to-year changes in the areal extent of the Sudd and surrounding wetlands are remarkably consistent with observed changes in the global atmospheric methane growth rate. This supports the idea that a large fraction of those recent annual changes in the atmospheric growth of methane are due to wetland emissions driven by changes in hydrology, particularly from Eastern Africa (Lunt et al 2021, Pandey et al 2021, Peng et al 2022, Qu et al 2022, Feng et al 2022b, 2023. The EO imagery data also represent additional information with which to constrain computational model parameters to improve the predictive capability of those models to describe hydrodynamics in continental-scale rivers.…”
Section: Discussionsupporting
confidence: 70%
“…The anomalous global atmospheric methane growth rates in 2020 (refs. 124,125 ) and 2021 (ref. 125 ) have also been partly attributed to anomalous Eastern African wetland emissions.…”
Section: Ecosystem Impactsmentioning
confidence: 99%